PERSEPSI DAN SIKAP TERHADAP KEBERAGAMAN: DAMPAKNYA TERHADAP PERILAKU SOSIAL - Ajeng Cahya Lestari; Annisa Khurrotul Luthfil Aiini, Alyaa Mahira, Suci Larosaty Putri, Sulistiasih (CV. ADIBA AISHA AMIRA, 2024)
Social perceptions, attitudes and social behavior in the context of human social interaction are discussed in this journal. Attitudes are formed through social interactions and learning that can influence a person's behavior, while individual characteristics and situations influence a person's social perceptions. Also discussed are contributions, nonverbal communication, the theory of reasoned action, and the effects of emotional distress following environmental disasters. The study of consumer attitudes also emphasizes attitudes, with discussions of attitude formation, theories explaining attitudes, attitude measurement techniques, the function of attitudes, and predictable relationships between attitudes and behavior. To understand human social interactions, these concepts are very important.